2008
DOI: 10.1124/dmd.108.020917
|View full text |Cite
|
Sign up to set email alerts
|

Rate-Limiting Steps in Hepatic Drug Clearance: Comparison of Hepatocellular Uptake and Metabolism with Microsomal Metabolism of Saquinavir, Nelfinavir, and Ritonavir

Abstract: ABSTRACT:The intrinsic metabolic clearance of saquinavir, nelfinavir, and ritonavir was determined over a range of concentrations (0.02-20 M) in both rat liver microsomes and fresh isolated rat hepatocytes in suspension. Clearance values were found to be concentration dependent for both systems, and at low concentrations, microsomal clearance was much greater (7-14-fold) than in hepatocytes. Kinetic parameters showed substantially lower microsomal K m values (5-42 nM) compared with suspended rat hepatocytes (3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
55
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(62 citation statements)
references
References 36 publications
5
55
2
Order By: Relevance
“…This behavior is consistent with the differences reported here in terms of K i values and the resulting Kp u, app . Interestingly, the ratio of microsomal to hepatocyte K m values (Parker and Houston, 2008) is similar to the corresponding ratio of K i values (Table 5).…”
Section: Discussionmentioning
confidence: 49%
See 3 more Smart Citations
“…This behavior is consistent with the differences reported here in terms of K i values and the resulting Kp u, app . Interestingly, the ratio of microsomal to hepatocyte K m values (Parker and Houston, 2008) is similar to the corresponding ratio of K i values (Table 5).…”
Section: Discussionmentioning
confidence: 49%
“…In contrast, the hepatic clearance of the protease inhibitors is very high (Shibata et al, 2000;Parker and Houston, 2008). We have studied this in some detail in vitro and have dmd.aspetjournals.org demonstrated that in hepatocytes the metabolic clearance is transporter rate-limited (Parker and Houston, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…10 Moreover, in addition to a carrier-mediated process, passive transmembrane permeation significantly contributed to the hepatic uptake of saquinavir and ritonavir. 11 In general, previous results imply that a carrier-mediated process is involved in the hepatic uptake of HIV PI.…”
Section: Introductionmentioning
confidence: 99%